Implementation of Extracurricular Curriculum in Instilling Character Education in MIS Pasar Bilah Labuhanbatu Utara - Mursal Aziz; Dedi Sahputra Napitupulu; Linda Hayati (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Character education in Indonesia is an important aspect of the education system, especially in shaping a generation that is not only intellectually intelligent but also has noble character. This study aims to analyze the implementation of the extracurricular curriculum in instilling character education at MIS Pasar Bilah, North Labuhanbatu. This study uses a qualitative approach with a phenomenological method to explore the experiences and perceptions of teachers, students, and the principal regarding the extracurricular curriculum implemented at the school. Data collection techniques were carried out through observation, interviews, and documentation studies. Data were analyzed using the Miles and Huberman analysis technique, with triangulation and member checking as techniques to guarantee data validity. The results of the study indicate that the extracurricular curriculum at MIS Pasar Bilah, which includes scouting, sports, and religious activities, plays a significant role in instilling character values such as discipline, responsibility, and cooperation among students. However, the main challenges faced are limited time and students' motivation to actively participate. This study also found that support from the school, teacher commitment, and parental involvement are crucial for the successful implementation of the character education program. The implications of this research provide insights for the development of extracurricular curricula in madrasas, particularly in improving the effectiveness of extracurricular activities as a means of character education. This research is expected to serve as a reference for other schools in strengthening character education through extracurricular activities.